Intra industry trade and product quality: China and eight developing countries - Eshraghi, Mastooreh; Ismail, Normaz Wana (College of Business, Feng Chia University, 2013)
This study aims to measure the export product quality improvement for trade between China and eight selected developing countries: Argentina, Brazil, Chile, Egypt, South Africa, Mexico, Turkey, and the Russian Federation based on disaggregated four-digit SITC data for the two periods 2000-2004 and 2004-2008. Vertical intra-industry trade high (VIITH) is considered as high quality products. The results revealed that the highest benefits of intra-industry trade with China are for South Africa in the first period and for Egypt in the second period. The highest positive growth of high quality products during the two periods is reported for Russia in the first period and for Brazil and Argentina in the second period. In conclusion, there is a massive potential for economic cooperation between China and these three partners.